Efforts to Enhance Gender-Based Health Promotion among Beneficiary Families of the Family Hope Program (PKH) in Sukoharjo Regency - Rahardjo, Budhi (AIBPM Publisher, 2024)
Gender equality-based health promotion for Family Hope Program (PKH) beneficiaries in Sukoharjo Regency aims to address disparities in healthcare access and awareness. The primary goal is to enhance knowledge and consciousness among PKH recipients, particularly regarding the importance of health maintenance. By achieving this objective, the initiative seeks to reduce preventable illnesses and enhance healthcare accessibility throughout Sukoharjo. Additionally, the program strives to promote gender equality in health-related decision-making, emphasizing the empowerment of women in health matters. The expected outcomes include an increase in health literacy among PKH beneficiaries and a more equitable distribution of healthcare resources. Furthermore, the implementation of gender-aware health promotion is anticipated to contribute to sustainable development goals and community well-being in Sukoharjo Regency Recommendations for future implementation include the development of comprehensive health education modules with a gender perspective and the integration of gender-focused policies into the PKH framework. By prioritizing these strategies, the program can foster positive behavioral changes and foster a more inclusive and equitable healthcare system for all PKH beneficiaries in Sukoharjo RegencyÂ .Keywords: gender, health promotion, PKH, Sukoharjo